Cerebrovascular Collateral Integrity in Pediatric Large Vessel Occlusion: Analysis of the Save ChildS Study. (25th January 2022) - Lee, Sarah; Jiang, Bin; Wintermark, Max; Mlynash, Michael; Christensen, Soren; Sträter, Ronald; Broocks, Gabriel; Grams, Astrid; Dorn, Franziska; Nikoubashman, Omid; Kaiser, Daniel; Morotti, Andrea; et al.
Abstract : Background and Objectives: Robust cerebrovascular collaterals in adult patients with large vessel occlusion stroke have been associated with longer treatment windows, better recanalization rates, and improved outcomes, but the role of collaterals in pediatric stroke is not known. The primary aim was to determine whether favorable collaterals correlated with better radiographic and clinical outcomes in children with ischemic stroke who underwent thrombectomy. Methods: This study analyzed a subset of children enrolled in SaveChildS, a retrospective, multicenter, observational cohort study of 73 pediatric patients with stroke who underwent thrombectomy between 2000 and 2018 at 27 US and European centers. Included patients had baseline angiographic imaging and follow-up modified Rankin Scale scores available for review. Posterior circulation occlusions were excluded. Cerebrovascular collaterals were graded on acute neuroimaging by 2 blinded neuroradiologists according to the Tan collateral score, in which favorable collaterals are defined as >50% filling and unfavorable collaterals as <50% filling distal to the occluded vessel. Collateral status was correlated with clinical and neuroimaging characteristics and outcomes. Between-group comparisons were performed with the Wilcoxon rank-sum test for continuous variables or Fisher exact test for binary variables. Results: Thirty-three children (mean age 10.9 [SD ±4.9]) years were included; 14 (42.4%) had favorable collaterals. Median final stroke volume as a percent of total brain volume (TBV) was significantly lower in patients with favorable collaterals (1.35% [interquartile range (IQR) 1.14%–3.76%] vs 7.86% [IQR 1.54%–11.07%], p = 0.049). Collateral status did not correlate with clinical outcome, infarct growth, or final Alberta Stroke Program Early CT Score (ASPECTS) in our cohort. Patients with favorable collaterals had higher baseline ASPECTS (7 [IQR 6–8] vs 5.5 [4–6], p = 0.006), smaller baseline ischemic volume (1.57% TBV [IQR 1.09%–2.29%] vs 3.42% TBV [IQR 1.26%–5.33%], p = 0.035), and slower early infarct growth rate (2.4 mL/h [IQR 1.5–5.1 mL/h] vs 10.4 mL/h [IQR 3.0–30.7 mL/h], p = 0.028). Discussion: Favorable collaterals were associated with smaller final stroke burden and slower early infarct growth rate but not with better clinical outcome in our study. Prospective studies are needed to determine the impact of collaterals in childhood stroke. Classification of Evidence: This study provides Class II evidence that in children with ischemic stroke undergoing thrombectomy, favorable collaterals were associated with improved radiographic outcomes but not with better clinical outcomes.